Propuesta psicológica para pacientes con estados depresivos que ingresan al área de quemados del Hospital General Isidro Ayora, durante el periodo abril - junio 2015 - Vallarades Torres, Iván Fernando (2015)
Burns are one of the most severe traumas that can be subjected in humans, not just because of the systemic changes that produce and the high therapeutic cost, are also because of psychological disorders and the serious consequences that remain after surgical treatment, that is greatly difficult the reintegration of these patients to society, generating primarily depression levels, for this reason the need of research on psychological approach to patients with depressive states that enter in the Burn Area of the General Hospital Isidro Ayora, during period April- June of 2015; this research propose the same objectives that were guided at determining depressive episodes experienced by patients admitted to the burn area of the General Hospital Isidro Ayora, during period April l-June of 2015; in identify the patients of burn area of the General Hospital Isidro Ayora, who have depressive episodes; besides of relate hospitalization with the depressive state of patients of burn area of the General Hospital Isidro Ayora; and finally, develop a proposal for psychological intervention that allows to face depressive episodes in patients of burn area of the General Hospital Isidro Ayora. The research was descriptive – analytics, cross or synchronous type, its purpose applied, and by the emphasis on nature it was quantitative and qualitative; were used methods as scientifics, descriptive, analytical-synthetic and statistical, among the techniques and instruments was applied the psychological observation, Beck test, in order to determinate the levels of depression, instruments that allowed to determinate that the majority of patients of Burn Area corresponds of male sex, besides it was possible to diagnose that 41% of surveyed have an average depression; 38% mild depression and finally the remaining 21% have moderate levels of depression, results, that suggests that the burns suffered by humans, affects them in their depression, from there the importance of intervening psychologically through a comprehensive treatment; that allows them to give through therapeutic techniques that contribute to face with their condition and therefore improve their emotional state, reducing the symptoms associated with depression, with a view to providing a better quality of life. Keywords: psychological care, burns, depression and intervention.